Systematics and evolution of the New Caledonian endemic genus Cazeresia (Coleoptera: Chrysomelidae, Eumolpinae) - Jesús Gómez-Zurita; Anabela Cardoso (Arthropod Systematics & Phylogeny)
In this work, we use a combined analysis of morphological and mtDNA sequence data to recognize and revise a group of species allied to the New Caledonian endemic leaf beetle genus Cazeresia Jolivet, Verma & Mille, 2005 of the Eumolpinae, considered monotypic before this work. We characterize and describe 20 new species allied to C. montana Jolivet, Verma & Mille, 2005 based on the recognition of morphological diagnostic traits and DNA-based species delimitation: C. australis sp. nov., C. clipeata sp. nov., C. corrugata sp. nov., C. globosa sp. nov., C. gracilis sp. nov., C. holosericea sp. nov., C. imperiosa sp. nov., C. impressicornis sp. nov., C. laevigata sp. nov., C. laticollis sp. nov., C. maquis sp. nov., C. ovata sp. nov., C. parentalis sp. nov., C. petitpierrei sp. nov., C. robusta sp. nov., C. spadicea sp. nov., C. subgeminata sp. nov., C. tibialis sp. nov., C. tricolor sp. nov. and C. wanati sp. nov. For C. globosa and C. spadicea we additionally describe the subspecies C. globosa altitudinalis ssp. nov. and C. spadicea bruna ssp. nov. We also propose transferring to this genus the species Thasycles humboldtiana Heller, 1916, Colaspis kanalensis Perroud, 1864, Dematochroma thyiana Jolivet, Verma & Mille, 2008 and Dumbea striata Jolivet, Verma & Mille, 2007, as C. humboldtiana (Heller) comb. nov., C. kanalensis (Perroud) comb. nov., C. thyiana (Jolivet, Verma & Mille) comb. nov. and C. striata (Jolivet, Verma & Mille) comb. nov., respectively. At present, the genus Cazeresia includes 25 species, the vast majority distributed in the southern part of Grande Terre in areas characterized by ultramafic soils and we speculate that the adaptation to these environmental characteristics in lowland areas may be ancestral in this lineage. Two thirds of the species are only known from their type locality, thus treated as potential microendemics, and most other have reduced ranges generally spanning few tens of kilometres. Finally, the degree of species sympatry or parapatry exhibited by Cazeresia is noteworthy, which in the absence of marked morphological differences among species suggests the possibility of the interplay of ecological mechanisms to minimize competition and exclusion.